SYSTEMATIC LITERATURE RIVIEW: PENGARUH SELF-COMPASSION TERHADAP KESEHATAN PSIKOLOGIS REMAJA - Rizky Amaliah Putri Almajid; Iriani Indri Hapsari; Zarina Akbar (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT Adolescence is a developmental stage characterized by rapid biological, emotional, and social changes, making individuals particularly vulnerable to psychological health problems. One protective factor that has received considerable attention in positive psychology is self-compassion; however, findings regarding its influence on various dimensions of adolescents' psychological health remain scattered across individual studies, highlighting the need for a comprehensive synthesis. This study aimed to examine the influence of self-compassion on emotion regulation, resilience, self-esteem, and subjective well-being among adolescents using a Systematic Literature Review (SLR) approach. The review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, including the stages of identification, screening, eligibility assessment, and inclusion of relevant studies. Literature was retrieved from Google Scholar using Publish or Perish with the keywords